Impactos sociales y ambientales que se ocasionan en la zona del caserío y en el parque turístico de Quistococha, distrito de San Juan - Aricari Marín, Graciela (2023)
This thesis is entitled "Social and environmental impacts that are caused in the area of the village and in the tourist park of Quistococha, district of San Juan". Its purpose is to know the indicators that cause social and environmental impacts such as quality of life, employment, pollution, as well as the evaluation of sound, air, water, drinking water, solid waste, landscape change, flora and fauna. in the environmental part and in the social part, attention to tourists and the strengthening of community culture and organization. The sample was determined by convenience, applied to 40 surveys of the villagers; On the other hand, the qualitative study was carried out with the Leopold Matrix. The methodology used was the technique of the questionnaire and observation. The hypothesis has been demonstrated, arriving to reject the hypothesis because the results of the Survey were very unfavorable; In the same way, the evaluation was carried out with the Matrix, confirming that the results of the observation are also very significant and negative, so the hypothesis was also rejected.